Seleksi Mikroba Endofit Curcuma Zedoria dalam Memproduksi Senyawa Kimia Antimikroba - Yoice Srikandace; Yatri Hapsari; Partomuan Simanjuntak (Fakultas Farmasi Universitas Pancasila, 2007)
It is well known, that temu putih (Curcuma zedoaria Berg.), a rhizome of the Zingiberaceae, is oftenly used as medicine. In this connection, the potential secondary metabolites as anticancer and antimicrobes are produced by endophytic microbes in the plant. In this research, five endophytic microbes from the Curcuma zedoaria’s rhizome were fermented to produce compounds as antimicrobes.